Unidades de conservação e conflitos ambientais no litoral sergipano, Brasil - Claudio Roberto Braghini; José Wellington Carvalho Vilar (Confins)
The coastal areas of Sergipe include protected areas among which it is worth mentioning the nature conservation units (UC). A UC is established as a space for environmental and territorial conflicts, when they restrict the use of resources by the communities living in the unit or its surroundings. Uses considered improper by management can be treated as pressures or threats on resources protected and seen as generating environmental or socio-environmental conflicts. In this context, this article aims to discuss environmental conflicts in conservation units of the coast of Sergipe. The pressures and threats were obtained from the context analysis of the RAPPAM - Rapid Assessment and Priority for Protected Area Management methodology. The three cases studied show environmental problems, as the actions or use for conservation proposed to the units are in opposition to other forms of land use, inherent to the coastal dynamics as a conflictive space in Sergipe. Conflicts are signaled and the instances of dialogue and consultation have the power to seek consensus solutions.